HAEMATOLOGY OF CAPTIVE RHESUS MACAQUES (Macaca mulatta) - M. Palanivel Rajan; M.G. Jayathangaraj; R. Sridhar; M. Parthiban (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Health status of non-human primates reared at Arignar Anna Zoological Park, Vandalur were determined by studying the haematolgoical parameters. A total of six Rhesus macaques aged from three to seven years were subjected to haematological analysis. Mean values of PCV, Hb, RBC, ESR, WBC, differential count and erythrocyte indices were studied. From this study, baseline information on haematology profile was obtained for the Rhesus macaques.